2023
DOI: 10.1021/acs.jmedchem.3c00815
|View full text |Cite
|
Sign up to set email alerts
|

Liquiritigenin Confers Liver Protection by Enhancing NRF2 Signaling through Both Canonical and Non-canonical Signaling Pathways

Abstract: Oxidative stress plays a critical role in drug-induced liver injury. In recent years, liquiritigenin (LQ), a natural flavonoid distributed in Glycyrrhizae Radix et Rhizoma (Gan Cao), shows protective effects against oxidative hepatotoxicity. However, the underlying mechanism remains unclear. In this study, we mainly investigated the role of NRF2, a core transcription factor in oxidative stress, in LQ-induced hepatoprotection. Our results indicated that the function of LQ to eliminate reactive oxygen species in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
(96 reference statements)
0
1
0
Order By: Relevance
“…, quercetin and its derivatives, catechin, and epigallocatechin 3-glucuronide) and phenols ( e.g. , gingerol) have shown anti-inflammation properties. , Liquiritigenin, a natural flavonoid, has been reported to protect against oxidative hepatotoxicity . While this exploratory network pharmacology analysis did not allow for precise identification of target pathways, the disease–gene–metabolite interaction network revealed that fermentation-enhanced metabolites possess potential therapeutic effects in mitigating colitis via regulating inflammation, oxidative stress, and lipopolysaccharide response pathways.…”
Section: Discussionmentioning
confidence: 97%
“…, quercetin and its derivatives, catechin, and epigallocatechin 3-glucuronide) and phenols ( e.g. , gingerol) have shown anti-inflammation properties. , Liquiritigenin, a natural flavonoid, has been reported to protect against oxidative hepatotoxicity . While this exploratory network pharmacology analysis did not allow for precise identification of target pathways, the disease–gene–metabolite interaction network revealed that fermentation-enhanced metabolites possess potential therapeutic effects in mitigating colitis via regulating inflammation, oxidative stress, and lipopolysaccharide response pathways.…”
Section: Discussionmentioning
confidence: 97%
“…The nuclear factor erythroid 2-related factor 2 (Nrf2) functions as a critical regulator of intracellular antioxidant mechanisms and forms an association with the antioxidant response element (ARE), prompting the upregulation of antioxidant genes that include NAD(P)H quinone oxidoreductase 1 (NQO1) and (HO-1) [54]. Nrf2 is activated mainly by entering the cell nucleus, and the translocation of Nrf2 is regulated by two main pathways, the canonical and non-canonical mechanisms [55]. In the canonical pathway, the Keap1-Nedd8-Cul3-Rbx1 complex sequesters the Nrf2 protein and facilitates the transfer of ubiquitin (Ub) proteins to the Neh2 domain in Nrf2.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that Licochalcone A activates the Nrf2/HO-1/NF-κB axis, inhibits pyrodeath and inflammatomes, and relieves osteoarthritis [60]. ISL activates the Nrf2 pathway through both classical and unclassical pathways, enhances antioxidant activity, and protects against liver damage [61]. ISL alleviates liver toxicity caused by rhubarb by activating the Nrf2 pathway and enhancing phase II metabolic enzymes [62].…”
Section: Discussionmentioning
confidence: 99%